Start shallow and grow deep: The development of a Hebrew reading brain. (5th November 2022) - Nathaniel, Upasana; Weiss, Yael; Barouch, Bechor; Katzir, Tami; Bitan, Tali
Abstract: Brain plasticity implies that readers of different orthographies can have different reading networks. Theoretical models suggest that reading acquisition in transparent orthographies relies on mapping smaller orthographic units to phonology, than reading opaque orthographies; but what are the neural mechanisms underlying this difference? Hebrew has a transparent (pointed) script used for beginners, and a non-transparent script used for skilled readers. The current study examined the developmental changes in brain regions associated with phonological and orthographic processes during reading pointed and un-pointed words. Our results highlight some changes that are universal in reading development, such as a developmental increase in frontal involvement (in bilateral inferior frontal gyrus (IFG) pars opercularis), and increase in left asymmetry (in IFG pars opercularis and superior temporal gyrus, STG) of the reading network. Our results also showed a developmental increase in activation in STG, which stands in contrast to previous studies in other orthographies. We further found an interaction of word length and diacritics in bilateral STG and the visual word form area (VWFA) across both groups. These findings suggest that children slightly adjust their reading depending on orthographic transparency, relying on smaller units when reading a transparent script and on larger units when reading an opaque script. Our results also showed that phonological abilities across groups correlated with activation in the VWFA, regardless of transparency, supporting the continued role of phonology at all levels of orthographic transparency. Our findings are consistent with multiple route reading models, in which both phonological and orthographic processing of multiple size units continue to play a role in children's reading of transparent and opaque scripts during reading development. The results further demonstrate the importance of taking into account differences between orthographies when constructing neural models of reading acquisition. Highlights: fMRI study of orthographic transparency in young and old Hebrew reading children. Children showed an age-related increase and left lateralization in IFG and STG. An interaction of transparency and length was found in STG & VWFA, across groups. Transparent script may rely on smaller units than reading a non-transparent script. Across both scripts, phonological abilities correlated with activation in the VWFA.